2023
DOI: 10.1001/jamanetworkopen.2023.32780
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Heat Exposure During Pregnancy and Severe Maternal Morbidity

Anqi Jiao,
Yi Sun,
Chantal Avila
et al.

Abstract: ImportanceThe rate of severe maternal morbidity (SMM) is continuously increasing in the US. Evidence regarding the associations of climate-related exposure, such as environmental heat, with SMM is lacking.ObjectiveTo examine associations between long- and short-term maternal heat exposure and SMM.Design, Setting, and ParticipantsThis retrospective population-based epidemiological cohort study took place at a large integrated health care organization, Kaiser Permanente Southern California, between January 1, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…During pregnancy, women are particularly sensitive to environmental temperature. In a retrospective cohort study, Jiao et al found that both long- and short-term maternal heat exposure increases the risk of severe maternal morbidity [ 54 ]. Among the physiological adaptations related to pregnancy, thermoregulation plays a pivotal role.…”
Section: Climate Change and Sex Differencesmentioning
confidence: 99%
“…During pregnancy, women are particularly sensitive to environmental temperature. In a retrospective cohort study, Jiao et al found that both long- and short-term maternal heat exposure increases the risk of severe maternal morbidity [ 54 ]. Among the physiological adaptations related to pregnancy, thermoregulation plays a pivotal role.…”
Section: Climate Change and Sex Differencesmentioning
confidence: 99%
“…There is a growing body of research on the deleterious effects of exposure to extreme ambient heat during pregnancy. 5 These include adverse birth outcomes such as preterm birth, 6 stillbirth, 7 congenital anomalies, 8 and low birthweight, 9 as well as adverse maternal health outcomes like hypertension, 10 preeclampsia, 11 gestational diabetes, 12 hemorrhage, 13 and infections. 14 Researchers have proposed several biological mechanisms through which extreme heat exposure can induce harm on both mother and fetus.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, maternal heat exposure is associated with an increased risk of both maternal morbidity and adverse pregnancy outcomes. 8 Despite multiple studies showing that extreme heat is associated with poor birth outcomes, 9 10 data on the underlying pathophysiological mechanisms remain sparse. 11 As work on effective and evidence-based interventions to reduce the health impacts of extreme heat develops at pace, this systematic review summarises our underlying knowledge of the impact of heat on maternal, placental and fetal physiology and highlights both knowledge gaps and potential pathways that could be considered in intervention studies.…”
Section: Introductionmentioning
confidence: 99%
“…12 Should these mechanisms be overwhelmed, then the core body temperature rises and adverse health effects are experienced, including heat illness, heat stroke and in pregnancy both maternal morbidity and adverse fetal outcomes. 8 9 16 …”
Section: Introductionmentioning
confidence: 99%